New legal challenges post covid with specific reference to Indian contract Act - SAFEER AHMED (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose: of the paper is to analyze new legal challenges faced by judicial fraternity in the implementation of law and its execution of justice post covid . As covid has transformed priorities of humanity all over the globe, along with specific reference to the most common law practiced in commercial world which is Indian contract act. Design /methodology: Based on the data available ,certain challenges faced by legal fraternity all over the globe was found .the inputs and information was also gathered from lawyers and judges who toil 24/7 to facilitate implementation of law precisely and constantly, further the researcher himself is a practicing advocate, who has come across different situations which were unique and oblivious. Findings : it was found that to ease the situations of legal implementation post covid many factors which although a part of general legal requirements but consider to be less significant has raised to the occasion like never before the factors such as specific performance of contract, loose and vague drafting ,conciliation and meditation became paramount ,further factor OF FORCE MAJURE (superior force or Act of God for emerge as game changer under Indian contract act. Limitations: The area of research was only confined to the problems faced by legal fraternity in court halls having live interaction there are various other problems like documentations and registration of cases which also need a very deep research to find root cause of problem and suggest the solution. Further research is only limited to Indian contract Act if properly analyzed there is a scope for not less than 10 to 12 different acts only under different commercial laws for deep study and solution exploration. Conclusion: Information and Communication Technology (ICT) is here to stay and hence legal fraternity of lawyers, judges, registers and above all *litigants* should be prepared to accept the fact even if there is no lock down there is no chance of live court halls functioning in near future. Virtual courts are the new normal further framers of any new policy should always take video and virtual court into consideration before framing any new policy.